Enhanced selective thermal emission with a meta-mirror following Generalized Snell's Law. Issue 1728 (21st April 2015) - Khan, M. Ryyan; Wang, Xufeng; Sakr, Enas; Alam, Muhammad A.; Bermel, Peter
ABSTRACT: Thermal emission plays a critical role in a wide variety of applications, including adjusting radiative losses in photovoltaics and selective solar absorbers, as well as enhancing the emission of high energy photons for thermophotovoltaics and photon-enhanced thermionic emission. In this work, we consider the benefit to thermal emission associated with replacing conventional mirrors with meta-mirrors following Generalized Snell's Law. By reflecting light at a different angle than incident, they can couple internally guided thermal radiation modes to the escape cone, ideally starting from any internally-guided angle. We illustrate the concept with two meta-mirror structures: a graded index material and a xylophone structure. Even without optimization, angle-averaged selective thermal emission is significantly enhanced compared to the planar case at selected wavelengths. Furthermore, the central wavelength and bandwidth of the enhancement can be matched with the requirements of each application.